Effect of EMS on seed germination in white seeded sesame varieties (Sesamum indicum L.): Effect of EMS on seed germination in white seeded sesame varieties (Sesamum indicum L.) - V SANDHIYA; M KUMAR; C PARAMESWARI; ANAND M BADIGANNAVAR (Journal of Oilseeds Research, 2020)
In the present investigation, two white seeded sesame varieties VRI 3 and SVPR 1 were treated with seven different concentrations of EMS. Germination percentage and germination index were tested using two different germination methods. Seed germination decreased with increased concentration of Ethyl Methane Sulphonate (EMS) in both the varieties. For fixing the lethal dose for the chemical mutagen Pro tray method of germination test was found reliable than germination paper method.